2008
DOI: 10.2119/2008-00035.gribar
|View full text |Cite
|
Sign up to set email alerts
|

No Longer an Innocent Bystander: Epithelial Toll-Like Receptor Signaling in the Development of Mucosal Inflammation

Abstract: Diseases of mucosal inflammation represent important causes of morbidity and mortality, and have led to intense research efforts to understand the factors that lead to their development. It is well accepted that a breakdown of the normally impermeant epithelial barrier of the intestine, the lung, and the kidney is associated with the development of inflammatory disease in these organs, yet significant controversy exists as to how this breakdown actually occurs, and how such a breakdown may lead to inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 190 publications
3
109
0
2
Order By: Relevance
“…Our findings further sustain the notion that airway epithelial cells orchestrate a defense response upon pathogen challenge by activating NF-B-and MAPK-dependent signaling pathways (56). In fact, activation of these pathways seems to be a central event of pathogen-exposed epithelial cells lining mucosal surfaces.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings further sustain the notion that airway epithelial cells orchestrate a defense response upon pathogen challenge by activating NF-B-and MAPK-dependent signaling pathways (56). In fact, activation of these pathways seems to be a central event of pathogen-exposed epithelial cells lining mucosal surfaces.…”
Section: Discussionsupporting
confidence: 84%
“…To date, there are 13 identified TLRs that recognize an assortment of PAMPs [i.e., lipopolysaccharide (TLR-4), peptidoglycan (TLR-2), flagellin (TLR-5) and bacterial DNA (TLR-9)]. All currently recognized TLRs are homologous with the IL-1 receptor, sharing an intracellular signaling domain, known as the Toll/IL-1R domain [131]. For example, the interaction of TLR-4 with lipolysaccharide leads to the activation of myeloid differentiation primary response protein 88-dependent signaling, resulting in the induction of pro-inflammatory genes such as TNF-α, IL-1β and IL-6 [132] (Fig.…”
Section: Mucosal Immune and Bacterial Defense Systemsmentioning
confidence: 99%
“…Epithelial-bacterial interactions that may occur via TLRs are likely to play roles in the regulation of processes that regulate barrier integrity, such as epithelial migration, proliferation, and apoptosis. During states of stress, such as hypoxia, TLR signaling becomes exaggerated in response to ligands, thus favouring mucosal barrier disruption and adversely affecting mucosal repair while worsening mucosal injury [131]. In recent proteomics studies on preterm pig intestinal tissue, we showed that heat shock proteins (e.g., HSP60 and GRP78) were increased after just 8 h of formula feeding [79,136,137], suggesting that stress proteins released in response to formula feeding may initiate the inflammatory cascade through TLRs.…”
Section: Mucosal Immune and Bacterial Defense Systemsmentioning
confidence: 99%
“…Expression of different pattern recognition receptors (PRRs) at mucosal surfaces is central to innate immune defences (Hall et al 2002, Gribar et al 2008, Saenz et al 2008. Among these PRRs, toll-like receptors (TLRs) have been the most extensively studied (Akira & Takeda 2004, Delbridge & O'Riordan 2007.…”
Section: Introductionmentioning
confidence: 99%